Influence of e-learning media on the quality of information systems student grades - Rosyadi, Muhammad Bachtyar; Surya, Maulidina Rahmawati (Jurnal Mandiri IT, 2024)
The purpose of this study was to determine the effect of e-learning learning media on the quality of information systems student grades; to provide exposure to e-learning learning media in information systems department; it is known the quality of student scores both the acquisition of the final score of each course and the GPA assessment of each semester as well as the presentation of attendance and the value of activeness in student learning. The type or method of this research is quantitative research with the SEM model which is a process of processing data previously obtained from respondents in the field or from quotations from trusted sources. In this study, statistical analysis will be used with the SmartPLS test. The research benefits obtained include exposure to effective and efficient e-learning learning media, so that it can be input in efforts to increase a high academic culture in the information systems department. The sample in the study was 20 students from the Information Systems Department. The analysis technique used is in the form of data from the results of giving questionnaires with descriptive analysis techniques to see tendencies, using a research and development approach. Results from research on e-learning learning media in the information systems department where e-learning can support the quality of student grades. The quality of grades here is not solely on the acquisition of the number of grade points from the course, but from all aspects, behavior, activity (fulfillment of assignments) that have been given.